1997
DOI: 10.1029/97jd00778
|View full text |Cite
|
Sign up to set email alerts
|

Experiments with a lunar atmospheric tidal model

Abstract: Abstract. A lunar tidal model similar to that of Forbes [1982] is used to investigate the effects of changes in background zonal winds on the structure of the lunar tide in the upper atmosphere. It is found that changes in the winds have a greater effect than changes in the background temperature profile with latitude. Observed changes in the structure of the lunar tide from year to year at Saskatoon may be explained by introducing stratospheric warmings into the model. The addition of an associated mesospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
101
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 27 publications
(31 reference statements)
10
101
0
Order By: Relevance
“…Some of the interannual variability can be accounted for by the influence of the underlying stratospheric winds (Stening et al, 1997a). However, the small amplitude of the lunar tide in the MLT region effectively limits our study to monthlymean properties and prevents the detailed investigation of the effects of stratospheric warmings etc.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the interannual variability can be accounted for by the influence of the underlying stratospheric winds (Stening et al, 1997a). However, the small amplitude of the lunar tide in the MLT region effectively limits our study to monthlymean properties and prevents the detailed investigation of the effects of stratospheric warmings etc.…”
Section: Discussionmentioning
confidence: 99%
“…A stratospheric sudden warming is a large-scale disturbance in the middle and lower atmosphere, which usually occurs during the northern winter. It has been shown that lunar atmospheric tides are subject to an amplification during stratospheric sudden warming events, which leads to enhanced lunar tidal effects in the ionosphere (Stening et al 1997;Pedatella et al 2012b;Forbes and Zhang 2012). The effect of stratospheric sudden warmings on the ionospheric dynamo will be discussed in more detail in Sect.…”
Section: Eejmentioning
confidence: 99%
“…Those tidal changes can result from changes in the mean flow (e.g., Stening et al 1997), interaction with planetary waves (e.g., Liu et al 2010;, and changes in the tidal sources (e.g., Goncharenko et al 2012). Besides, Forbes and Zhang (2012) suggested that a change in the resonance property of the atmosphere during stratospheric sudden warming events leads to a significant increase in the amplitude of semidiurnal lunar tides.…”
Section: Stratospheric Sudden Warming Effectmentioning
confidence: 99%
“…Vial and Forbes (1994) provided a much improved model which showed reasonable agreement with observations. This model was extended to greater heights using the Global Scale Wave Model (GSWM) of Hagan et al (1995) (see Stening et al, 1997a). Results from the extended model gave fair agreement with analysed data at the near equatorial site of Christmas Island (Stening et al, 1997b).…”
Section: Introductionmentioning
confidence: 91%
“…Some experiments with the GSWM model showed quite large changes in phase and amplitude of the lunar tide were associated with stratwarms which occur during the northern winter. These changes were particularly noticeable at observing stations near 50°N latitude (Stening et al, 1997a). The phases for those measurements, in which the error bar of the amplitude extends below zero, are likely to be unreliable.…”
Section: Year-to Year Variationsmentioning
confidence: 99%